Multicast Radar Data Transmission Using the Tunnel in Tunnel Method and IGMP (Internet Group Management Protocol) Filtering by Utilizing the Internet Network - Atmaka, Ekky Widha; Hartoko, Adhitya Wisnu (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
This research proposes the implementation of multicast radar data transmission using the tunnel in tunnel method by utilizing the installed IP VPN network. The background of this study is the failure in radar data transmission resulting in a change of service from surveillance to procedural service, as well as the impact of the Covid-19 pandemic on aviation organizations. The purpose of this implementation is to enhance flight safety while achieving cost efficiency for the company. Objectives include changing transmission methods, budget efficiency, improving operational safety, compliance with international standards, and support for the concept of flight information management. Advantages of multicast radar data transmission include centralized IP base, ease of monitoring, and the use of FO converters for surge protection. Implementation is based on aviation regulations, international standards, and partnership contracts. Contingency plans cover network and device failure scenarios. Cost benefit analysis shows significant financial gains from this implementation. It is hoped that this research will make a positive contribution to improving efficiency and operational safety in aviation.